First Line Platinum Based Chemotherapy in Malignant Testicular Germ Cell Tumours – A Single Institutional Observational Study - Basu, Praloy (Asian Pacific Journal of Cancer Biology, 2025)
Background: Testicular germ cell tumours (TGCTs) are the most common solid malignancy in young men, with excellent prognosis due to the efficacy of platinum-based chemotherapy. However, prospective data from low- and middle-income countries like India are limited. Materials and methods: This prospective observational study was conducted over two years at a tertiary care hospital in western India. Eligible patients with newly diagnosed malignant testicular GCTs received platinum-based chemotherapy per NCCN 2024 guidelines. Baseline and treatment-related parameters were documented. Treatment response was assessed via RECIST 1.1, and toxicities were graded using CTCAE v5.0. Progression-free survival (PFS) was estimated using the Kaplan-Meier method. Results: Among 51 registered patients, 34 were eligible. Median age was 34.5 years. Seminoma and non-seminomatous GCT (NSGCT) were equally represented. Most patients (59%) presented with Stage III disease. All patients underwent radical orchiectomy followed by chemotherapy. BEP was the most common regimen. Grade 3 toxicity was rare; pulmonary toxicity occurred in three patients. Overall radiological response rate was 94% (CR 53%, PR 41%), with higher CR in seminoma (76%) than NSGCT (35%). Median follow-up was 11.25 months, with a PFS rate of 91.2%. PFS was 100%, 85%, and 85% in good, intermediate, and poor risk groups, respectively. Conclusions: Platinum-based chemotherapy remains highly effective and well tolerated in TGCTs, even in resource-constrained settings. Despite delays in diagnosis and treatment, outcomes in this Indian cohort were comparable to global standards, supporting continued adherence to established treatment protocols.